The Allied Health Professions : A Sociological Perspective - Nancarrow, Susan; Borthwick, Alan (Alan M.) (Book collections on Project MUSE., 2021)
Drawing on case studies from optometrists, physiotherapists, pedorthists and allied health assistants, this book offers an innovative comparison of allied health occupations in Australia and Britain. Adopting a theory of the sociology of health professions, it explores how the allied health professions can achieve their professional goals.